Isolation and Characterization of Probiotics from Various Food Samples - P. V. Kamala Kumari (Journal of Global Pharma Technology, 2019)
Probiotics are living organisms that are used as food additives with beneficial effects on the healthy body by setting microbial balance in gastrointestinal tract. Lactic acid bacteria (LAB) as protective cultures are common probiotic organisms that are considered safe due to having specific characteristics. Main genera of LAB are Leuconostoc, Enterococcus, Lactobacillus, Lactococcus, Bifidobacterium, Pediococcus, and Streptococcus. These bacteria cause reduction of gastrointestinal diseases by increasing benefit microorganisms growth and reducing pathogens population mechanisms.Several therapeutic applications for probiotics can be cited protection against traveller's diarrhea, prevention of urogenital diseases, reduction of hypercholesterolemia, alleviation of constipation, prevention of food allergy and osteoporosis and protection against bladder and cancer.  In addition to, probiotics can be prevention or treatment of some disorders, such as lactose malabsorption, irritable bowel syndrome, acute diarrhea, mild forms of inflammatory bowel disease and necrotizing enterocolitis.The present study aims in isolation of probiotics from various daily household food samples available easily in Indian market.